ADAPTING DRY-MASONRY BRICK HOUSE SYSTEM AS A GREEN CYCLE MODEL FOR SOUTH EAST ASIAN MARKETS - Khamidi, M. Faris; Matsufuji, Yasunori; Yamaguchi, Kentaro (RILEM, 2004)
In Japan, construction and demolition waste amounts to 20% of all the industrial waste and this accounts for more than 70% of all illegal dumping. Since 1970, Waste Management Law has been enacted and further amended in year 2000 to tailor to the more specific needs in dealing with construction waste under “Construction Material Recycling Law” (enforced in spring 2002). It is necessary to note that there are many factors which prevent the recycling of construction waste and one of the main reasons is that due to the nature of current construction method, various materials used in the construction industry are mixed when buildings are demolished. Adapting a dismantling and recycling friendly building methods is one of the remedy that may well solve the problems that have been plaguing the construction industry for years. Since October, 1997, a group of researchers led by Prof. Yasunori Matsufuji of Kyushu University has embarked a R&TD in what is called Dry-masonry1 Brick House System (DBHS) that utilized a construction method called “Steel Reinforced Brick construction based on Distributed Unbonded Prestress theory” (SRB-DUP) as a tactic to carry out a sustainable strategy to reduce waste generation. This paper discusses how developing countries in South East Asia region namely Malaysia and Indonesia can adapt DBHS as a “Green Cycle” model that may well conform to the overall Sustainable Development Plan of these two countries in particular minimizing construction and demolition waste generation.